Synergistic effects of HMG‐CoA reductase inhibitor and angiotensin II receptor blocker on load‐induced heart failure. Issue 5 (10th April 2018) - Ito, Yusuke; Maejima, Yasuhiro; Tamura, Natsuko; Shiheido‐Watanabe, Yuka; Konishi, Masanori; Ashikaga, Takashi; Hirao, Kenzo; Isobe, Mitsuaki
Abstract : 5‐Hydroxy‐3‐methylglutaryl‐CoA reductase inhibitors (statins) have beneficial effects in patients with heart failure (HF), regardless of serum cholesterol levels. However, their synergic effects with angiotensin II receptor blocker (ARB) remain to be established. We assessed the existence and potential underlying mechanisms of the effects of combined ARB [losartan (LOS)] and statin [simvastatin (SIM)] on cardiac function in rats and mice with load‐induced HF. Salt‐loaded Dahl salt‐sensitive (DS) rats were treated with vehicle, LOS, SIM, or LOS + SIM for 8 weeks. To mimic load‐induced HF in vitro, cultured neonatal rat cardiomyocytes (NRCM) were cyclically stretched. We also investigated the effect of LOS + SIM on pressure overload‐induced HF using mice with transverse aortic constriction (TAC). LOS + SIM improved left ventricular (LV) function and reduced LV hypertrophy more than the monotherapies in both salt‐loaded DS rats and TAC‐operated mice. LV‐tissue increases in Rho kinase and matrix metalloproteinase‐9 activity were decreased to a greater extent by LOS + SIM than by LOS and SIM monotherapies. Plasma levels of Exp‐3174, a LOS metabolite, were higher in LOS + SIM‐treated DS rats than in LOS‐treated rats. Stretch‐induced hypertrophy of NRCM pretreated with SIM + Exp‐3174 was significantly attenuated from that with LOS, Exp‐3174, SIM, or LOS + SIM. SIM administration significantly enhanced mitophagy in mouse hearts after TAC. However, LOS + SIM reduced mitophagy, and the salutary effect of SIM in mouse hearts after TAC was abolished in AT1R −/− mice. In conclusion, LOS and SIM have beneficial myocardial effects on load‐induced HF via differential pleiotropic effects. Thus, combination therapy of these drugs thus has potential as a therapeutic strategy for HF. Abstract : Here, we show the beneficial effect of combined angiotensin II receptor blocker (ARB) and statin on cardiac function in rodents' load‐induced heart failure models. Co‐treatment with ARB and statin improved cardiac remodeling in these models compared with that of either drug individually via differential pleiotropic effects. Thus, combination therapy of these drugs has potential as a therapeutic strategy for heart failure.